The bad beginning - Snicket, Lemony; Helquist, Brett (New York : HarperCollins Publishers, 1999)
After the sudden death of their parents, the three Baudelaire children must depend on each other and their wits when it turns out that the distant relative who is appointed their guardian is determined to use any means necessary to get their fortune.
Keywords: Orphans -- Fiction; Brothers and sisters -- Fiction; Humorous stories